Wideband slot antenna for WLAN access points - Medeiros, Carla R. (2013)
This letter presents a new printed slot antenna with cavity back for wireless local area network (WLAN) access points (base stations) providing wideband operation bandwidth at least from 2.5 to 4.8 GHz. The design is based upon an ultrawideband (UWB) antenna configuration modified with the inclusion of a cavity back in order to produce stable unidirectional radiation pattern. The new configuration also ensures a stable linear polarization with cross-polarization level below 20 dB. Results are confirmed with measurements. Not disregarding other applications, the new design is especially adequate for multiple-input–multiple-output (MIMO) space and polarization diversity arrangements, presenting low cross polarization and very low coupling to adjacent elements.